Sedimentology and sequence stratigraphy of the late-Messinian - Early pliocene continental to marine deposits of the Boudinar basin (North Morocco). (February 2019) - Merzeraud, Gilles; Achalhi, Mohammed; Cornée, Jean-Jacques; Münch, Philippe; Azdimousa, Ali; Ben Moussa, Abdelkhalak
Abstract: During the Messinian Salinity Crisis (MSC), between 5.97 and 5.33 Ma, the marine connections between the Atlantic Ocean and the Mediterranean Sea were temporarily restricted. The post-MSC reflooding of the Mediterranean Sea by the Atlantic waters and its sedimentary record are debated. The Boudinar basin (North-Morocco) provides an exceptional record of this period between ca 5.32–5.27 and 4.37 Ma at youngest (Zanclean - Zone PL1). The sedimentary succession of this basin comprises seven facies associations corresponding to depositional settings ranging from continental to open marine environments. We provide a new sequence stratigraphic framework, based on twelve stratigraphic sections. Two orders of depositional sequences (4th, 3rd order), related to base-level changes during the Late-Messinian Early-Pliocene time interval, are correlated at the basin scale. According to our reconstruction, the post-MSC base level rise and the Zanclean reflooding lasted from a minimum of several tens up to hundreds thousands years, suggesting a gradual, not catastrophic event indicative of a progressive transgression. Highligths: Two orders of sequences (4 th, 3 rd order) were correlated during the Late-Messinian Early-Pliocene. The sea-level drop during the Messinian Salinity Crisis (MSC) was of limited amplitude. The post-MSC transgression does not match with the rapid and sudden reflooding scenario.